Effects of additional knowledge of results on modifying highly practiced acyclic swimming techniques with knowledge of performance - Krause, D. (International Journal of Sports Science & Coaching, 2017)
The author investigated the effects of additional knowledge of results on modifying swimming starts and turns with video-based knowledge of performance. A total of 18 swimming experts (15-18 years of age) learned modifications of start and turn techniques with knowledge of performance or a combination of knowledge of performance and knowledge of results. The feedback condition was switched between the groups from experiment 1 to experiment 2. Both experiments contained 50 trials with augmented feedback distributed over five sessions. Both experiments revealed no detrimental effects of additional knowledge of results on process-related performance variables. With respect to the result-related variables (start time and turn time), only the groups without knowledge of results exhibited temporary impairment in the immediate retention tests. The results are largely replicated in both experiments. Knowledge of results seems to have positive effects on modifying with knowledge of performance. The presence of knowledge of results might reduce the deautomatizing conscious control processes that are induced by knowledge of performance and might cause temporary performance impairments. ABSTRACT FROM AUTHOR